Structures of human cytosolic and mitochondrial nucleotidases: implications for structure-based design of selective inhibitors - Pachl, Petr; Fábry, Milan; Rosenberg, Ivan; Simák, Ondřej; Rezáčová, Pavlína; Brynda, Jiří (Acta crystallographica. Section D, Biological crystallography, 2014)
The human 5'(3')-deoxyribonucleotidases catalyze the dephosphorylation of deoxyribonucleoside monophosphates to the corresponding deoxyribonucleosides and thus help to maintain the balance between pools of nucleosides and nucleotides. Here, the structures of human cytosolic deoxyribonucleotidase (cdN) at atomic resolution (1.08 Å) and mitochondrial deoxyribonucleotidase (mdN) at near-atomic resolution (1.4 Å) are reported. The attainment of an atomic resolution structure allowed interatomic distances to be used to assess the probable protonation state of the phosphate anion and the side chains in the enzyme active site. A detailed comparison of the cdN and mdN active sites allowed the design of a cdN-specific inhibitor.
Keywords: eukaryotické buňky; orgánová specificita; hydrolases; Molecular Docking Simulation; nukleotidasy; Organophosphonates; Escherichia coli; Mitochondria; Eukaryotic Cells; simulace molekulového dockingu; Enzyme Inhibitors; Structure-Activity Relationship; lidé; rekombinantní proteiny; Recombinant Proteins; krystalografie rentgenová; deoxyribonukleotidy; mitochondrie; Models, Molecular; Phosphates; organofosfonáty; Protein Conformation; molekulární modely; katalytická doména; racionální návrh léčiv; inhibitory enzymů; Catalytic Domain; structure-based drug design; konformace proteinů; Drug Design; vztahy mezi strukturou a aktivitou; cytosol; Organ Specificity; Nucleotidases; Deoxyribonucleotides; Cytosol; Isoenzymes; 5′(3′)-deoxyribonucleotidases; Crystallography, X-Ray; fosfáty; izoenzymy; enzyme inhibition; Humans